High performance solid state solar cells incorporating CdS quantum dots and CH3NH3PbI3 perovskite. (2019) - Givalou, Lida; Antoniadou, Maria; Kaltzoglou, Andreas; Falaras, Polycarpos
Abstract: Since 2012, halide perovskites CH3 NH3 PbX3 (X = Cl, Br, or I) have been the topic of intensive research due to their excellent structural, optical and electronic properties and their application to perovskite solar cells (PSCs). PSCs are a new type of third-generation photovoltaics presenting low cost, ease of construction and power conversion efficiencies (PCEs) exceeding 23%, challenging the Si-based devices. This work describes a novel solution processed PSC structure: FTO/TiO2 (CL)/mp-TiO2 /CdS/Perovskite/Spiro-MeOTAD/Ag, using co-sensitization of quantum dots (QDs) with perovskite materials. This new cell architecture improves the device performance and characteristics and gives us the opportunity to develop solid state QDs cells.